Expression of transferrin receptors on mitogen-stimulated human peripheral blood lymphocytes: relation to cellular activation and related metabolic events. - Galbraith, R M (1981)
Mitogen-activated normal human peripheral blood lymphocytes bind transferrin to specific membrane receptors. In this study, lymphocytes stimulated with phytohaemagglutinin for 0-66 hr were examined to determine the relation of this phenomenon to cellular activation and related metabolic events. Transferrin receptors were first detected at 20-24 hr. This event was consistently preceded by RNA and protein turnover which commenced during the first 6 hr of culture, whereas initiation of DNA synthesis was detected concurrently with the appearance of receptors or slightly later (24-30 hr). Exposure of cells to inhibitors of RNA and protein synthesis early during culture (at 0 or 24 hr) prevented the expression of transferrin receptors, but also caused generalized metabolic failure, and abrogated cellular activation. In contrast, later addition of these agents at 48 hr did not interfere significantly with the process of activation, but did suppress the terminal increase in receptor-bearing cells observed during the final 18 hr in control cultures lacking inhibitor. After deliberate thermal stripping of receptors from activated cells, the reappearance of membrance binding sites which normally occurred within 30 min, was also blocked by cycloheximide, puromycin and actinomycin D. However, similar inhibition of DNA which was induced by hydroxyurea had much less effect upon both the initial appearance of receptors and their reappearance after ligand-induced depletion. These results demonstrate that the appearance of transferrin receptors upon human lymphocytes is dependent upon cellular activation and requires synthesis of protein and RNA.